2020
DOI: 10.21203/rs.3.rs-25051/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-cell RNA seq analysis identifies the biomarkers and differentiation of chondrocyte in human osteoarthritis

Abstract: Background: Single-cell RNA sequencing (scRNA-seq) was recently adopted for exploring molecular programmes and lineage progression patterns of pathogenesis of important diseases. In this study, scRNA-seq was used to identify potential markers for chondrocytes in osteoarthritis (OA) and to explore the function of different types of chondrocytes in OA.Methods:Here we aimed to identify the biomarkers and differentiation of chondrocyte by Single-cell RNA seq analysis. GeneOntology (GO) and Kyoto Encyclopedia of Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Collagen binding, ECM binding and structural ECM functions were previously reported following analysis of candidate marker genes of chondrocytes in human osteoarthritis reporting an enrichment of the molecular function of collagen binding. It has also previously been suggested that the integrin-binding sialoprotein (IBSP) interacts with collagen and appears to modulate cell-matrix interactions [ 113 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collagen binding, ECM binding and structural ECM functions were previously reported following analysis of candidate marker genes of chondrocytes in human osteoarthritis reporting an enrichment of the molecular function of collagen binding. It has also previously been suggested that the integrin-binding sialoprotein (IBSP) interacts with collagen and appears to modulate cell-matrix interactions [ 113 , 114 ].…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) has been applied for uncovering molecular programs and lineage progression of OA ( Zhang et al, 2020c ). For instance, Zhang et al (2020c) identified the biomarkers and differentiation of chondrocytes in human OA using scRNA-seq analyses.…”
Section: Introductionmentioning
confidence: 99%
“…Single-cell RNA sequencing (scRNA-seq) has been applied for uncovering molecular programs and lineage progression of OA ( Zhang et al, 2020c ). For instance, Zhang et al (2020c) identified the biomarkers and differentiation of chondrocytes in human OA using scRNA-seq analyses. Moreover, Ji et al (2019) adopted scRNA-seq analyses to reveal chondrocyte taxonomy and mechanisms of human OA cartilage regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a breakthrough single-cell RNA-seq study revealed the progression of human OA by defining seven chondrocyte populations, including proliferative chondrocyte, prehypertrophic chondrocytes, hypertrophic chondrocytes (HTCs), fibrocartilage chondrocytes (FCs) and three novel populations with distinct functions ( 77 ). In another single-cell expression profiling research, HTC, homeostatic chondrocyte and FC were characterized in 480 chondrocyte samples ( 23 ). Furthermore, the study compared the transcriptional program and all major cell populations in patient groups between KBD and OA.…”
Section: Molecular Markers For Oa and Joints At Single-cell Resolutionmentioning
confidence: 99%